Synthesis and Screening of 3-Formyl-2-thio-1,2,3,4-tetrahydro pyrimidine Analogues as Antibacterial Agents - Satyavathi, K.; Kiran, T. Naga Ravi; Raju, P. Bhoja; Sharmila, M. (Asian Journal of Chemistry, 2010)
5-Acyl-6-methyl-4-substituted-2-thio-1,2,3,4-tetrahydropyrimidines were prepared by cyclocondensation between appropriate aldehyde, acetoacetate and thiourea using aluminium chloride and conc. hydrochloric acid. These compounds upon treatment with dimethyl formamide and phosphorous oxychloride furnish the title compounds. The structures of these compounds have been confirmed on the basis of their analytical, IR and NMR spectral data. The title compounds have been tested for antibacterial activity against Eshcereshia coli, Bacillus subtilis, Staphylococcus epidermidis and Staphylococcus aureus. They have also been tested for antifungal activity against Aspergillus niger and Penicillium chrysogenum.